The role of interfascial plane blocks in multimodal chronic pain management: PENG block+pulsed radiofrequency+ozone therapy for hip osteoarthritis - Alıcı, Hacı Ahmet; Çiftçi, Bahadır; Alver, Selçuk; Ahıskalıoğlu, Ali; Bilal, Bora; Tulgar, Serkan (NLM (Medline), 2023)
[Abstract Not Available]
The role of interfascial plane blocks in multimodal chronic pain management: PENG block plus pulsed radiofrequency plus ozone therapy for hip osteoarthritis
Keywords: Ozone Therapy; PENG Block; Pulsed Radiofrequency; Chronic Pain Management